Dynamic Molecular Interphases Regulated by Trace Dual Electrolyte Additives for Ultralong‐Lifespan and Dendrite‐Free Zinc Metal Anode - Chen, Hong‐Bo; Meng, Huan; Zhang, Tong‐Rui; Ran, Qing; Liu, Jie; Shi, Hang; Han, Gao‐Feng; Wang, Tong‐Hui; Wen, Zi; Lang, Xing‐You; Jiang, Qing (Angewandte Chemie International Edition, 2024)
Metallic zinc is a promising anode material for rechargeable aqueous multivalent metal‐ion batteries due to its high capacity and low cost. However, the practical use is always beset by severe dendrite growth and parasitic side reactions occurring at anode/electrolyte interface. Here we demonstrate dynamic molecular interphases caused by trace dual electrolyte additives of D‐mannose and sodium lignosulfonate for ultralong‐lifespan and dendrite‐free zinc anode. Triggered by plating and stripping electric fields, the D‐mannose and lignosulfonate species are alternately and reversibly (de‐)adsorbed on Zn metal, respectively, to accelerate Zn2+ transportation for uniform Zn nucleation and deposition and inhibit side reactions for high Coulombic efficiency. As a result, Zn anode in such dual‐additive electrolyte exhibits highly reversible and dendrite‐free Zn stripping/plating behaviors for >6400 hours at 1 mA cm−2, which enables long‐term cycling stability of Zn||ZnxMnO2 full cell for more than 2000 cycles. Hybrid aqueous electrolyte of ZnSO4 with trace dual electrolyte additives of D‐mannose and sodium lignosulfonate enables ultralong‐lifespan and dendrite‐free Zn metal anode by virtue of D‐mannose and lignosulfonate species alternately and reversibly adsorb on Zn surface to form dynamical molecular interphases and enter Zn2+ solvation sheath to boost de‐solvation kinetics. Zn anode in such dual‐additive electrolyte exhibits exceptional stability for >6400 hours.